Effects of growth hormone and insulin-like growth factor I on rabbit proximal convoluted tubule transport. - Quigley, R (1991)
This in vitro microperfusion study examined the effects of growth hormone and insulin-like growth factor I (IGF-I) on proximal convoluted tubule (PCT) transport. Tubules were perfused with an ultrafiltrate-like solution and bathed in a serum-like albumin solution. Neither a physiologic (5 x 10(-10) M), nor a pharmacologic (5 x 10(-8) M) dose of growth hormone had an effect on PCT phosphate or bicarbonate transport, or volume absorption. Addition of 5 x 10(-9) M and 5 x 10(-8) M IGF-I, but not 5 x 10(-10) M IGF-I, to the bathing solution resulted in an increase (12-15%) in phosphate transport, but no change in volume absorption or bicarbonate transport. Addition of IGF-I to the luminal perfusate also stimulated phosphate transport. The effect was noted at a concentration of 5 x 10(-11) M IGF-I (27% stimulation) and was maximal at a concentration of 5 x 10(-10) M IGF-I (46% stimulation). There was no effect of luminal IGF-I on volume absorption or bicarbonate transport. These data indicate that growth hormone has no direct effect on PCT transport. In the PCT, IGF-I stimulates phosphate transport specifically and acts via both basolateral and apical membranes. However, the magnitude of the maximal response to the luminal addition of IGF-I was threefold greater than that measured upon addition of the hormone to the bath, and the stimulation occurred at a 100-fold lower concentration. These data are consistent with IGF-I mediating the in vivo stimulation of phosphate transport by growth hormone.